Best practice in the management of primary nocturnal enuresis in children: a systematic review - Hodgkinson, B.; Josephs, K.; Hegney, Desley (University of Adelaide, 2010)
Objective- Nocturnal enuresis is the involuntary loss of urine at night in a child of an age and physical health where they would be expected to be dry. The prevalence of this condition in Australia has been estimated at 18.9% in children 5 to 12 years of age, with up to 19% of boys and 16% of girls aged 5 years wetting the bed at least once per month. Up to the age of 13 years bedwetting is more common in boys and more common in girls after this age. Nocturnal enuresis has a spontaneous cure rate of approximately 14% however up to 3% of children remain enuretic as adults. Although this condition is pathologically benign, it can have serious social and psychological repercussions for the sufferer including affects on self esteem, school success, parental disapproval and even sexual activity in later life. Despite the volume of information available for the management of enuresis, the majority of research has been conducted outside Australia. Therefore, the purpose of this work was to produce management guidelines for nocturnal enuresis in children specific to Australian clinical practice. Inclusion criteria- This review considered systematic reviews or concurrently controlled trials (randomised controlled trials (RCT), pseudo-randomised controlled trials, controlled clinical trials (CCT), interrupted time series (ITS) and controlled before and after trials (CBA)), for examining effectiveness of interventions to manage nocturnal enuresis in children up to the age of 16 years.Search strategy- A systematic search of the literature was performed to identify all available evidence. Cochrane and other health technology assessment websites were searched for existing systematic reviews. For recent randomised controlled trials and controlled trials (1990 to 2007) Pubmed, Embase, and CINAHL databases were searched. Reference lists of all retrieved articles were searched for relevant trials. These reviews and guidelines were summarised and presented to an advisory panel of nurse continence advisors and clinicians to ensure relevance to Australian clinical practice. Methodological quality- Methodological quality of all studies was assessed by two reviewers using the JBI critical appraisal forms for experimental studies located within the JBI-MAStARI software. This tool was used to identify all sources of bias. Where disagreement existed between the two reviewers a third reviewer adjudicated. Results- Seven systematic reviews, eight new trials and two guidelines were used in the development of these guidelines.Briefly management recommendations include: Symptoms of daytime wetting should be addressed prior to managing nocturnal enuresis; Initial management should be simple interventions such as behavioural methods (e.g. rewards), journal keeping and the management of constipation. Star charts were seen to be effective in some small trials; Failing these measures, alarm based interventions have been shown to be highly effective and are based on good quality trials. Approximately 2/3 of children become dry compared to no treatment; Desmopressin may be used in some situations as a temporary measure and/or in conjunction with alarm therapy; While lifting and waking interventions were also associated with significantly fewer wet nights these methods are not recommended; The evidence for the use of complementary interventions such as hypnosis, psychotherapy, acupuncture or chiropractic is mixed and requires further evaluation.Conclusions- Despite the high prevalence of nocturnal enuresis and the negative psychosocial sequelae that can arise from this condition, management is both readily available and effective. Implications for practice- The practice of managing nocturnal enuresis in children should start with addressing both daytime wetting and any evidence of constipation. Following this, less invasive behavioural therapies should be attempted. If these measures fail then the use of alarms with or without short-term administration of desmopressin could be attempted. Other interventions have yet to be proven to be definitively effective and should be considered with caution. It should be emphasized however, that the vast majority of children will become continent at some future time point, with or without the benefit of interventions. Implications for research- While it is clear that some behavioural methods, alarms and desmopressin can be effective interventions, the evidence for other treatments is not so definitive. The observation however that even alarms and/or desmopressin do not work for all children suggests that research to establish the effectiveness of other interventions (especially behavioural and complementary treatments) should be performed in the form of large, carefully designed RCTs.